Three new species in Calamus sect. Podocephalus (Arecaceae: Calamoideae) from the Philippines, Indonesia, and Papua New Guinea - Fernando, Edwino Samson (Phytotaxa, 2014)
Three new species in Calamus sect. Podocephalus (Arecaceae: Calamoideae) are described and illustrated: Calamus daemonoropoides from the Philippines, Calamus parutan from East Java and Bali, Indonesia, and Calamus zieckii from Papua and West Papua, Indonesia and Papua New Guinea. These are compared with similar species in the section.